The Effect of Performance Allowance and Work Discipline on Employee Performance at the Lembang Agricultural Training Center (BBPP) - Gempur Putra Pratama; Nurul Hermina (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This study aims to determine the performance allowance, work discipline and employee performance at the Lembang Agricultural Training Center (BBPP), as well as to determine how the influence of work allowance and work discipline on employee performance at the Lembang Agricultural Training Center (BBPP). Work allowance is one of the factors that can affect the performance of an employee. Every employee has hopes and desires to get remuneration in the form of allowances in accordance with the workload they get. Another factor that is thought to have an impact on employee performance is the work discipline factor. The application of work discipline is carried out to improve employee behavior and work ethics when working. Employee performance at the Lembang Agricultural Training Center (BBPP) did not run optimally because the employees had not been able to achieve the desired target which caused a decrease in company productivity. The research method used is descriptive and verification methods. The sample used in this study were all employees who worked at the Agricultural Training Center (BBPP) Lembang. The sampling technique used is saturated sampling or census. Data processing is done by using multiple linear regression, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Based on the results of the study, it can be concluded that there is a significant effect between work allowances on employee performance at the Lembang Agricultural Training Center (BBPP) and there is a significant influence between work discipline on employee performance at the Lembang Agricultural Training Center (BBPP) and there is a significant influence between work allowances and work discipline on employee performance at the Lembang Agricultural Training Center (BBPP).